Investigation on the impact of quality characteristics and storage stability of foxtail millet induced by air cold plasma - Wang, Lang-Hong; Li, Zhongyan; Qin, Jiale; Huang, Yanyan; Zeng, Xin-An; Aadil, Rana Muhammad (Frontiers in Nutrition, 2022)
The aim of this work was to investigate the effects of dielectric barrier discharge-air cold plasma (DBD-ACP, 15-35 kV, 2-12 min) on the quality of foxtail millets. The L and b* values were evaluated by a digital colorimeter representing the color of millets were significantly changed at 25 kV for 4-12 min or at 35 kV for 2 to 12 min. The results were consistent with the change of total yellow pigment in millets, indicating that DBD-ACP damaged the carotenoids if the treatment condition was too high. The activity of lipoxygenase and lipase, involving the oxidation and hydrolysis of lipids of millet, decreased significantly induced by DBD-ACP. For example, the lipoxygenase and lipase activity of Mizhi millet was decreased from 44.0 to 18.7 U g-1min-1, 56.0 to 15.1 U/(mg pro) (p＜0.05) after being exposed to 25 kV for 2 to 12 min, respectively. Changes of color, lipoxygenase and lipase activity, malondialdehyde content of millets were determined during accelerated storage (40 ± 2 °C and 75% Relative Humidity) for 15 days after being treated by DBD-ACP under 15 and 25 kV for 4 min. Results showed that millets treated by DBD-ACP at 15 kV kept a better color with lower malondialdehyde content, and lower lipoxygenase and lipase activity compared to control. This work implied that DBD-ACP is an underlying approach for the storage of foxtail millets.